Export Barriers to halal food processing small and medium enterprises (SMEs) in Malaysia - Ismail, Mohd Mansor; Islam, Md. Saiful; Wan Bakar, Wan Mohd Marzuki (Universiti Putra Malaysia Press, 2013)
The aim of this research is to examine the factors obstructing the Malaysian halal food processing SMEs in their exporting efforts. Enhancing the export performance of halal food processing industry is crucial in materializing Malaysia’s dream of becoming global halal hub envisaged in Third Industrial Master Plan (IMP3), 2006-2020. The data was generated from 181 randomly selected SMEs from 12 states of Malaysia engaged in exporting halal processed foods through a structured questionnaire. Factor analysis, Kaiser- Myer- Olkin (KMO), and Reliability tests were conducted in order to derive perceptions of SME exporters about export barriers. The results indicate that procedural barriers are more obstructive than internal and external barriers. Non recognition of food quality assurance certificate, high tariff, inadequate tax incentives to encourage export, lack of government assistance to overcome export barriers, very high standards for export products, delays in payment, inadequate market information and need of excessive documentation and paper work were viewed as crucial procedural barriers to export. The result of the study will help halal food manufacturers and exporters to be more serious in attaining competitiveness and setting suitable business strategies to sustain their presence in competitive international markets. It will also help the support providing agencies of public and private sectors to modify the existing policies or formulate new ones in favor of halal food processing SMEs.